2019
DOI: 10.1021/acschemneuro.9b00147
|View full text |Cite
|
Sign up to set email alerts
|

Computational Insight into the Mechanism of the Irreversible Inhibition of Monoamine Oxidase Enzymes by the Antiparkinsonian Propargylamine Inhibitors Rasagiline and Selegiline

Abstract: Monoamine oxidases (MAO) are FAD-containing flavoenzymes that catalyze the degradation of a range of brain neurotransmitters, whose imbalance is extensively linked with the pathology of various neurological disorders. This is why MAOs have been the central pharmacological targets in treating neurodegeneration for more than 60 years. Still, despite this practical importance, the precise chemical mechanisms underlying the irreversible inhibition of the MAO B isoform with clinical drugs rasagiline (RAS) and seleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 96 publications
3
34
0
Order By: Relevance
“…More importantly, this was followed by the quantum mechanics (QM) cluster calculations [ 54 ] at the DFT level, which revealed that the MAO inactivation proceeded through a three-step reaction, where, in the rate-limiting first step, the MAO enzyme used the FAD’s N5 atom to abstract a hydride anion from the inhibitor’s α-CH 2 group ( Figure 2 ), being in a full analogy with the MAO catalytic mechanism [ 55 , 56 , 57 , 58 ], thus confirming that both SEL and RAS are mechanism-based inhibitors. The complete reaction profile led from the bound inhibitors to the corresponding N5(FAD)-adducts, the latter being in excellent agreement with the crystallographic data on the inhibited enzyme, and further confirmed a better reactivity of SEL through both its lower activation barrier and higher overall exergonicity [ 52 ]. Still, although the obtained relative difference in the activation free energies among inhibitors of ΔΔ G ‡ = 1.2 kcal mol −1 was found to be in excellent agreement with the measured k inact values, which predicts a difference of ΔΔ G ‡ EXP = 1.7 kcal mol −1 , the absolute values of Δ G ‡ (SEL) = 27.9 kcal mol −1 and Δ G ‡ (RAS) = 29.1 kcal mol −1 clearly exceeded those predicted experimentally, although these were significantly lower than those calculated for several alternative mechanistic scenarios.…”
Section: Introductionsupporting
confidence: 62%
See 2 more Smart Citations
“…More importantly, this was followed by the quantum mechanics (QM) cluster calculations [ 54 ] at the DFT level, which revealed that the MAO inactivation proceeded through a three-step reaction, where, in the rate-limiting first step, the MAO enzyme used the FAD’s N5 atom to abstract a hydride anion from the inhibitor’s α-CH 2 group ( Figure 2 ), being in a full analogy with the MAO catalytic mechanism [ 55 , 56 , 57 , 58 ], thus confirming that both SEL and RAS are mechanism-based inhibitors. The complete reaction profile led from the bound inhibitors to the corresponding N5(FAD)-adducts, the latter being in excellent agreement with the crystallographic data on the inhibited enzyme, and further confirmed a better reactivity of SEL through both its lower activation barrier and higher overall exergonicity [ 52 ]. Still, although the obtained relative difference in the activation free energies among inhibitors of ΔΔ G ‡ = 1.2 kcal mol −1 was found to be in excellent agreement with the measured k inact values, which predicts a difference of ΔΔ G ‡ EXP = 1.7 kcal mol −1 , the absolute values of Δ G ‡ (SEL) = 27.9 kcal mol −1 and Δ G ‡ (RAS) = 29.1 kcal mol −1 clearly exceeded those predicted experimentally, although these were significantly lower than those calculated for several alternative mechanistic scenarios.…”
Section: Introductionsupporting
confidence: 62%
“…While we were not able to locate the corresponding literature data for rasagiline, we can assume that its p K a value should be roughly the same. Our earlier mechanistic proposal required unionized inhibitors to undergo the MAO inhibition [ 52 ], since it is significantly easier to detach the hydride anion from the neutral system and generate the carbocation, than it is from the already monocationic system that is transformed into dicationic compounds upon the hydride abstraction. This is justified considering the mentioned p K a value for selegiline being close to the physiological pH value, but also knowing the hydrophobic nature of the MAO active site, which was clearly demonstrated experimentally [ 5 , 34 ] and confirmed computationally [ 69 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of the rest of the protein environment was considered with the CPCM implicit solvation model using a dielectric constant of ε = 4.0, as suggested by Himo and co-workers [28], and a dielectric constant of ε = 78.4 for the aqueous solution, all in line with our previous reports [13], where we also demonstrated that a potential increase in the former dielectric constant to ε = 20.0 lowers the accuracy of the obtained results and even predicts wrong trends among ligands. Additionally, in our experience, such a truncated cluster-continuum model of the entire protein turned very useful in rationalizing various aspects of the catalytic activity [29], selectivity [30] and inhibition [31] of the monoamine oxidase family of enzymes, and is broadly used by different groups to decipher various biological phenomena [32][33][34][35][36], which justifies its use here. We note in passing that, despite its practical usefulness, the proposed value of ε = 4 is, in some cases, apparently too small to prevent the proton transfer from protonated to anionic residues, which then occurred spontaneously during the geometry optimization, provided the involved pair is in close vicinity.…”
Section: Computational Detailsmentioning
confidence: 97%
“…The binding free energies, Δ G BIND , of each ligand within the Pf Hsp90 ATP binding site were calculated using the established MM-GBSA protocol [ 35 , 36 ] available in AmberTools16 [ 32 ], and in line with our earlier reports [ 15 , 37 , 38 ]. MM-GBSA is a widely used method for binding free energy calculations from snapshots of MD trajectory with an estimated standard error of 1–3 kcal mol −1 [ 36 ].…”
Section: Methodsmentioning
confidence: 99%